Rapid prototyping platform for Saccharomyces cerevisiae using computer-aided genetic design enabled by parallel software and workcell platform development - Rajakumar,PD; Gower,G; Suckling,L; Kitney,R; McClymont,D; Freemont,P (Slas Technology, 2019)
Biofoundries have enabled the ability to automate the construction of genetic constructs using computer-aided design. In this study, we have developed the methodology required to abstract and automate the construction of yeast-compatible designs. We demonstrate the use of our in-house software tool, AMOS, to coordinate with design software, JMP, and robotic liquid handling platforms to successfully manage the construction of a library of 88 yeast expression plasmids. In this proof-of-principle study, we used three fluorescent genes as proxy for three enzyme coding sequences. Our platform has been designed to quickly iterate around a design cycle of four protein coding sequences per plasmid, with larger numbers possible with multiplexed genome integrations in Saccharomyces cerevisiae. This work highlights how developing scalable new biotechnology applications requires a close integration between software development, liquid handling robotics, and protocol development.